The impact of digital transformation on green total factor productivity of heavily polluting enterprises - Han, Jiabin; Sun, Ruyu; Zeeshan, Muhammad; Rehman, Alam; Ullah, Irfan (Frontiers in Psychology, 2023)
As a result of the digital transformation, high-quality economic development and environmental protection have become key engines of economic growth. However, green total factor productivity (GTFP), as an indicator that comprehensively reflects economic and environmental benefits, there is a lack of studies that analyze the effect of digital transformation on heavily polluting enterprises’ GTFP from a micro perspective, and its impact mechanism is still unclear. To investigate the impact of digital transformation on heavily polluting enterprises' GTFP and its mechanism, we use data from Chinese A-share listed enterprises in the heavily polluting industry from 2007 to 2019. The results show that digital transformation can significantly enhance heavily polluting enterprises’ GTFP, and this finding still holds after considering the endogenous problem and conducting robustness tests. Digital transformation can enhance heavily polluting enterprises’ GTFP by promoting green innovation, improving management efficiency, and reducing external transaction costs. The improvement role of digital transformation on heavily polluting enterprises’ GTFP is more obvious in the samples of non-state-owned enterprises, non-high-tech industries, and the eastern region. Compared with Blockchain technology, artificial intelligence technology, cloud computing technology, big data technology, and digital technology application can significantly improve heavily polluting enterprises’ GTFP. There are a number of limitations to the existing research that are addressed in our paper. It contributes to the theoretical enrichment of the literature in terms of digital transformation and GTFP, besides it also provides practical policy implications for promoting, supporting and facilitating the digital transformation of high polluting enterprises and thus facilitating their high-quality development and growth.